Prescription Pattern and Drug Utilization Analysis in Patients with Acute Coronary Syndrome - Saju, Dona; Joy, Cristina; Moorthy, Moushmi Arul; Wilson, Bivin; Antony, Jithin; Singaravel, Sengottuvelu; Sherief, Sheik Haja; Thangavel, Sivakumar (Indian Journal of Pharmacy Practice)
Background: Acute Coronary Syndrome (ACS) is one of the major causes of morbidity and mortality in developing countries, which illustrates the need for rational prescribing of drugs to the patients. Aim: The aim of the study is to analyse the prescription pattern and drug utilisation for the drugs prescribed to the patients with ACS by checking the compliance with the standard guidelines provided by the American College of Cardiology/American Heart Association (ACC/AHA). Materials and Methods: A prospective observational study for a period of 6 months was conducted in the cardiology and cardiothoracic departments of a tertiary care hospital. The sample size was determined by using Rao software and percentage of the data was calculated using Microsoft Excel 2007. Results: A total of 270 patients were enrolled in the study in which males (219) dominated females (51) and were found in the age group of 60-69 years (92). Diabetes (62.9%) followed by hypertension (54.8%) were found to be the dominant risk factors. The prescribing frequency of dual antiplatelet therapy, statins, beta blockers, angiotensin converting enzyme inhibitors/angiotensin receptor blockers and nitrates was 93.3%, 97.3%, 94.1%, 76.3% / 14.1% and 41.2%. The treatment given to the patients was not completely in compliance with the ACC/ AHA guidelines (18.14%). Conclusion: The study provides an overall insight of the pattern of drugs prescribed to the patients with ACS which reveals the necessity of improving the rational prescribing of drugs in accordance with the standard guidelines.
Keywords: Acute Coronary Syndrome; Prescription pattern; ACC/AHA guidelines; Rational drug use; Compliance.